Metode Interpolasi Linear dalam Analisis Suku Bunga Kredit Berdasarkan Pembayaran Angsuran: Studi Kasus Pembiayaan Mobil New Agya 1.2 E M/T - Abidin, Nurwahidah; Sri Dewi Anugrawati; Asriani Hasan (Universitas Islam Negeri Alauddin Makassar, 2024)
An interest rate is the price or amount of additional payment paid by the borrower to the lender. The interest rate is usually not shown in the loan instalment brochure. This study aims to analyse the effective interest rate of vehicle financing loans. The method used to determine the effective interest rate in this study is linear interpolation. The calculated interest rates are flat interest rates and effective interest rates. Determining the most profitable car financing alternative for customers can be seen from the lowest interest rate. This study analyses the case of New Agya 1.2 E M/T car price through Kalla Toyota Palopo branch and credit through Mandiri Utama Finance at the end of 2023. Based on the results of data processing using the linear interpolation method, it is found that the higher the instalment payment and the smaller the tenor offered, the lower the interest rate.